Dicobalt orthosilicate-graphitic carbon nitride nanocomposites as promising visible-light nanocatalysts for removal of water-soluble organic dyes - Masoud Hosseini; Mojgan Ghanbari; Makarim A. Mahdi; Mohammed H. Almaamori; Zainab Abbas Abd Alhassan; Masoud Salavati-Niasari (Applied Water Science)
Abstract This paper reports the preparation of cobalt silicate (Co2SiO4, CSO) first by a cost-effective and simple sonochemical route, followed by the fabrication of Co2SiO4/g-C3N4 (CSO/CN) nanocomposites with different mass ratios by ultrasonic-assisted co-precipitation. We have investigated the photocatalytic performance of Co2SiO4, g-C3N4, and different Co2SiO4/g-C3N4 nanocomposites for the degradation of eriochrome black T (EB). This initial instance of CSO integrated with CN demonstrates a superior function in photocatalysis. The outcomes indicated that multiple parameters affected effectiveness, including the amount of CSO, catalyst, and EB. As a result, CSO/CN with a weight ratio of 0.1:1 is the most efficient, which means that 0.07 g of CSO/CN (0.1:1) is capable of degrading 90.0% of 10 ppm EB. Photodegradation reactions were demonstrated by the scavenger tests to be largely influenced by superoxide radicals. The kinetic investigation showed that a bigger rate constant (k = 0.0166 min‒1) leads to higher efficiency (90.0%). The combination of CSO and CN as composites shows great potential for efficient photocatalytic dye degradation applications. Advanced materials for environmental treatment procedures may be developed as a result of further research and development in this field.